1997
DOI: 10.1038/sj.ijo.0800351
|View full text |Cite
|
Sign up to set email alerts
|

Achievement of near-normal body weight as the prerequisite to normalize sex hormone-binding globulin concentrations in massively obese men

Abstract: OBJECTIVE: To investigate the effects of weight loss on sex hormone-binding globulin (SHBG) in massively obese males and whether normal SHBG concentrations could be obtained regardless or not of the achievement of normal body weight values. DESIGN AND SUBJECTS: Sera were collected for SHBG determination from 63 massively obese men, partly before they underwent biliopancreatic diversion (pre-op group 11) and partly during the post-surgical follow up (post-op group 52), and twenty normal weight healthy control m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 12 publications
1
13
0
2
Order By: Relevance
“…Low levels of SHBG have been associated with obesity (26), and weight loss in obese men has normalized SHBG levels (33). It has been suggested that SHBG levels probably are related to general metabolic factors.…”
Section: Variation With Anthropometrymentioning
confidence: 99%
“…Low levels of SHBG have been associated with obesity (26), and weight loss in obese men has normalized SHBG levels (33). It has been suggested that SHBG levels probably are related to general metabolic factors.…”
Section: Variation With Anthropometrymentioning
confidence: 99%
“…6,[10][11][12] Furthermore, it also has been demonstrated that not only BPD, but also other bariatric operations, may result in substantial clinical improvement in patients with type 2 diabetes. 7,[11][12][13][14][15][16][17][18][19][20][21] Since many of these procedures controlled diabetes in obese and nonobese individuals, which procedure is best? To find the answer, we studied the effect of ileal transposition (IT) and BPD in Goto-Kakizaki (GK) rats, the most widely used animal model of nonobese type 2 diabetes.…”
mentioning
confidence: 99%
“…48,49 Moreover, achievement of near-normal body weight can lead to normalisation of SHBG concentrations in massively obese men. 50 Nevertheless, determination of the relative importance of these bidirectional effects in our cohort is not possible as there could be differences in short-and long-term relationships between adiposity and testosterone.…”
Section: Discussionmentioning
confidence: 98%